Sosialisasi Pembuatan Hairdum Berbahan Alami Daun Bambu (Bambusa SP) yang kaya akan vitamin E dan Antibiotik Untuk Mengatasi Masalah Rambut Bercabang Di Kalangan Remaja : Socialization of Making Hairdum Made from Natural Bamboo Leaves (Bambusa SP) which is rich in vitamin E and Antibiotics to Overcome Split Hair Problems Among Teenagers - Puspasari, Ainur Kharisma; Rosemawati, Amelia Diesta Choirunia; Iqlima, Isna Fatimatul; Khasanah, Linaria Arofatul Ilmi Uswatun (Jurnal Pengabdian Magister Pendidikan IPA, 2025)
Split ends are often experienced by teenagers, especially girls, and can be caused by various factors such as excessive sun exposure, use of chemical-based products, air pollution, and bad hair care habits. One solution that can be used to overcome this problem is to use natural ingredients, such as bamboo leaves, which are rich in vitamin E and antibiotic properties. This research aims to socialize the making of hairdum (hair mask) made from bamboo leaves to teenagers in Tlanak Village, Kedungpring District. This activity was carried out on October 16, 2024 at the Tlanak Village Hall with the method of counseling, practical training, and direct assistance in making hairdum. The socialization results showed that teenagers were very enthusiastic and interested in the benefits of bamboo leaves for hair health. Participants were also taught how to make Hairmist from bamboo leaves as a more natural and environmentally friendly alternative to hair care. This program is expected to increase teenagers' understanding of natural hair care and reduce dependence on chemical-based products. In addition, this program also encourages the utilization of local natural resources to develop products that are socially and economically beneficial. The results of this activity show a positive impact on adolescents' awareness of the importance of natural hair care, as well as opening up opportunities for product development.